(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
DeepCData is a research project on the use of composite materials for tidal turbines, with partners Composite Testing Laboratory (CTL), the University of Galway and Ocean Renewable Power Company (ORPC) in Ireland. One of the main objectives of the project is to conduct a test campaign on novel composite materials for tidal turbine blades, to support research into long-term product performance. The test campaign will also evaluate the use of sustainable composite materials (e.g. bio-based or recyclable materials) to quantitatively establish the trade-offs for emissions reduction, lifetime costs and mechanical performance. The project expands the current state-of-the-art for tidal turbines by generating test data related to (a) long-term performance of materials following water immersion; (b) mechanical properties for novel, sustainable materials; and (c) comprehensive fatigue testing data. A suite of tensile and compressive tests establishes the baseline properties for the selected materials. The results of fatigue testing, residual strength testing and post-immersion testing then provide data for analyses of the long-term performance of blades for their design life. The open-source data produced in this project will enable tidal device developers to conduct feasibility assessments of their own technologies and improve their forecasts of levelized cost of electricity (LCOE). This paper presents the material selection process and initial test campaign results from the DeepCData project. The materials were selected using the design requirements for the ORPC RivGen 2.1 turbine hydrofoils. Material selection involved reviewing available material data in the literature and from commercial material suppliers to select suitable types of composites for hydrofoil applications. After down-selection, four materials were identified to represent competitive manufacturing methods for the hydrofoils. Each material has characteristics that make it interesting for further investigation, e.g. a low void content prepreg from Hexcel, a low-cost carbon epoxy from A&P Technologies, an infusible thermoplastic resin from Arkema and a novel powder epoxy material from ÉireComposites. The test matrix was developed to meet the requirements for material properties for tidal turbine design. The material properties were determined in line with the DNV standard for tidal turbine design (DNVST-0164). Two of the selected materials will be fully characterized for dry and immersed conditions. While the tests identified for the remaining two materials consider select key properties that require deeper investigation before either material can be considered for use in a commercial application. The results of the campaign will be made available through an open-source database for the tidal energy community. There are only two similar datasets on composite materials, one is for conventional wind turbine materials, however, it does not contain the type of testing critical for tidal turbine design and the focus is primarily on glass-fibre reinforced polymers. There is also a comparable dataset for aerospace-grade materials, however, due to the high cost and emissions required to produce these materials, they are unsuitable for tidal turbine applications. Therefore, the dataset produced as part of this project will be an invaluable resource to the tidal sector and will help support technology developers to scale their devices.